Solaris 8 administrator's guide - Watters, Paul A. (O'Reilly, 2002)
The Solaris operating system, along with related Sun products like Java, is one of the most reliable and scalable platforms on which to build e-commerce products, and on which to support all networked services. Yet, one problem that potential users face is finding out more information about what Solaris offers. In a sense, they want to know how much technical work is involved in migrating to Solaris, and what kind of philosophy Solaris is based on. To answer these questions, Solaris 8 Administrator's Guide covers all aspects of deploying Solaris as a network server, including both basic and advanced network services. Given newfound interest in Solaris as an enterprise network operating system, this guide is aimed squarely at supporting enterprise-level services. It's written for experienced network administrators who want an objective guide to networking with Solaris, and covers installation on both the Intel and Sparc platforms. With it, you will learn how to setup Solaris as a file server, application server, and database server. In its coverage of advanced topics, Solaris 8 Administrator's Guide offers examples of configuration files and the installation of third-party software packages. This comprehensive book also contains more conceptual and difficult material that is absent from other Solaris reference manuals. At all points, emphasis is placed on issues like evaluating the security, scalability, and reliability of specific software packages--at the expense of providing detailed coverage of every available package. The book covers the practical experience and new skills needed to understand the impact of new services and new software products on existing server systems. Author Paul Watters--a recognized authority on Solaris--avoids so-called "historical" services, like UUCP, which can easily fill chapters but are not commonly found in today's production environments. Indeed, he doesn't bother to provide an in-depth history of Solaris or UNIX at all, assuming that you can find this material elsewhere. Instead, the practical focus is on supporting relevant contemporary networking technologies. Solaris 8 Administrator's Guide provides you with a third-party view that not only praises Solaris, but is critical and realistic in its assessment. This book is for experienced Solaris Administrators as well as and those looking to migrate to this operating system.